Struggling divas: notes for a study of Las divas de mi barrio [Divas of my Neighborhood] by Carmen Montañez - Lorenzo-Feliciano, Violeta (Universidad Pedagógica y Tecnológica de Colombia, 2016)
his paper I will discuss how Montañez redefines the term “diva” in her collection of short stories Las divas de mi barrio Divas of my neighborhood ]. I argue that this redefinition, values the role of female characters who differ physically from the ideas of beauty that tend to be associated with a diva. This is significant since these characters belong to the working class of the country where the plot develops. Thus, these short stories pay tribute to other forms of femininity and knowledge that tend to be excluded from the status quo for not going along with aesthetic preferences and behaviors that reinforce machismo.